The Effect of Human Resource Management Practices on Employee Performance - et.al, Shahid Mahmood (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present study examines the relationship between HRM practices and performance of employee to be tested in Punjab police, Pakistan. The sample size in this study is 368 respondents that consists of Inspectors and Sub-inspectors of Punjab Police Department in Pakistan. We collected data using questionnaire and analysis using Smart-PLS. Our result discovered that job rotation, training and development, compensation, career planning, and performance appraisal have a positive affect to Employee Performance in Punjab Policy department, Pakistan. Based on our findings, we suggest the policymakers to provide more intensive compensation to employees, optimizing job rotation, implementing training and development, provide appropriate career planning, and making advance performance appraisal in order to improve the performance of Punjab police employees in Pakistan. This study extends existing literature of Employee Performance, it delivers new understandings on the conception and role of job rotation, training and development, compensation, career planning, and performance appraisal to stimulate the reformation of Employee Performance in the government institution such as the Punjab police department.